Optimal taxation of risky entrepreneurial capital - Corina Boar; Matthew T. Knowles (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
We study optimal taxation in a model with endogenous financial frictions, risky investment and occupational choice, where the distribution of wealth across entrepreneurs affects how efficiently capital is used. The planner chooses linear taxes on wealth, capital and labor income to maximize the steady state utility of a newborn agent. Most agents in the model are poor, leading to a redistributive motive for taxation. Optimal tax rates can be written as a closed-form function of the size of the tax bases and their elasticities with respect to tax rates. We find that it is optimal to tax capital income because financial frictions reduce the elasticity of capital income with respect to taxes and because capital income taxes prevent excessive entry into entrepreneurship. Optimal wealth taxes are positive but close to zero, since they strongly discourage capital accumulation.
Keywords: E2; E6; H2; 330; entrepreneurship; financial frictions; taxation